Lexical outcomes of Karelian-Russian bilingualism in Tver Karelian - Tavi, Susanna (Eesti ja soome-ugri keeleteaduse ajakiri. Journal of Estonian and Finno-Ugric Linguistics, 2022)
This study investigates the language contact between Tver Karelian and Russian, attempting to provide a comprehensive overview of the lexicon of bilingual code. The methodology includes a combination of statistical analyses and handling contact-induced change in terms of the Code-Copying Framework (=CCF). Nine interviews with nine people were conducted using the memory walk method. In code copying, correlations were found between different word classes and contact-relatedness. In code alternation, few differences were found between different speakers and one commonality was the use of complex numerals as Russian phrases without adapting them into the Tver Karelian code. The findings confirm that the copies are of a certain kind and appear in certain word classes. Code alternation sequences suggest that, according to the CCF, the discourse rather than the language is mixed. The findings within CCF have implications on minority language policies, as the findings support the use of bilingual terminology. Kokkuvõte. Susanna Tavi: Karjala-vene kakskeelsuse mõju tverikarjala keele sõnavarale. Käesolevas uurimistöös uuritakse tverikarjala ja vene keele kontakte. See uuring püüab anda tervikliku ülevaate kakskeelse koodi sõnavarast. Metoodika sisaldab kombinatsiooni statistilistest analüüsidest ja kontaktidest põhjustatud muutuste käsitlemisest koodikopeerimise raamistiku (Code-Copying Framework = CCF) osas. Üheksa intervjuud üheksa inimesega viidi läbi mälukõnni meetodil. Leiti seoseid erinevate sõnaklasside ja kontaktidega seotuse vahel. Koodivahelduses leiti eri kõnelejate vahel vähe erinevusi ja üheks ühiseks jooneks oli keerukate arvsõnade kasutamine venekeelsete fraasidena, ilma neid tverikarjala koodi sobitamata. Leiud kinnitavad, et koopiad on teatud liiki ja esinevad teatud sõnaklassides. Koodi vaheldumise jadad viitavad sellele, et CCF-i kohaselt on segatud eelkõige diskursus, ja mitte keel. CCF-i leiud avaldavad mõju vähemuskeelte poliitikale, kuna leiud toetavad kakskeelse terminoloogia kasutamist.